Le Bois dans l'Art Contemporain. (Brussel : Théâtre National de Belgique, 1974)
Anthoons, Willy ; Bury, Pol ; Caille, Pierre ; Cantré, Jozef ; Claus, Louis ; Constant ; De Clerck, Oscar ; Delahaut, Jo ; De Winne, Robert ; Dusepulchre, Francis ; Gentils, Vic ; Glibert, Jean ; Glorie, Raymond ; Godart, Jean ; Jadot, Maurice ; Laenen, Jean-Paul ; Laffineur, Marc ; Lavachery, Michel ; Martini, Remo ; Mathys, Lode ; Minne, Joris ; Pleyers, Jean ; Smolders, Michel ; Toussaint, André ; Vaes, Francis ; Van Craeynest, Pierre ; Vandercam, Serge ; Verbanck, Geo ; Willame, Jean ; Willequet, André ; Wolfers, Marcel ; Wybaux, Fritz ; Deuse, Pierre
biografie
boek